Bacterial Detection Causing Subclinical Mastitis on Etawah Crossbreed Goat in Kokap, Kulon Progo, Yogyakarta Province - Clara Ajeng Artdita; Morsid Andityas; Nur Ika Prihanani; Yohanes Wawan Budiyanto (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2020)
Resident in Kokap, Kulon Progo, Yogyakarta Province has another income sector, that is dairy goat (Etawah Crossbreed) farming and they have been joining into farm group, which is called Kelompok Ternak. There are many bacteria that causing dairy goat intra mamary infection, thus the milk production will be contaminated. Two hundred and four (204) milk samples from 103 lactation goat in four farm groups in Kokap, Kulon Progo, Yogyakarta is used in this study. Out of these, 21 samples (10,29%) were detected strong positive (++ and +++) for subclinical mastitis by using California Mastitis Test (CMT). Among this positive result, the next step was bacteria detection. This tests were held in Preclinic Laboratory Animal Health Study Program, Vocational School, UGM. The samples were inoculated in blood agar, then colony was identify by Gram staining. The next steph is biochemical tests using McConkey Agar (MCA) and eosin methylene blue (EMB) as a selective media for Gram negative bacteria, manitol salt agar (MSA) as selective media for Staphylococcus, sugar fermented broth (glucose, lactose, mannitol, maltose, and sacharose), Kigler iron agar (KIA), lysine iron agar (LIA), motility indole ornithin (MIO), and Simmon’s citrate. The result was Staphylococcus aureus (80%), Staphylococcus epidermidis (20%), Escherichia coli (10%), and Klebsiella pneumoniae (10%).